Indigenous Technical Knowledge used, in dairying, by Pastoralists of Jammu and Kashmir - RANI, KAVITA (Indian Journal of Dairy Science, 2023)
The study was carried out in Union Territory of Jammu & Kashmir. Two district Rajouri & Poonch from Jammu division were selected purposively because of being the districts of highest Gujjar population. Two districts Anantnag & Baramulla from Kashmir division were selected purposively because of being the districts of highest Bakarwal population. Sixty respondents (Gujjars) from migratory tracts of district Rajouri & Poonch from Jammu division were selected randomly and sixty respondents (Bakarwal) from migratory tract of districts Anantnag & Baramulla from Kashmir division were selected randomly comprising a total of 120 respondents. Pastoralists those who were rearing at least 10 milch animals were selected for the study. Focus group discussion method was used for collection of data related to Indigenous Technical Knowledges (ITKs). The discussion revealed that the respondents were using ITKs primarily in breeding, feeding and health-care management practices. With regard to the induction of heat, thirty per cent of the respondents used chapatti of a mixture of Gur and ghee in the ratio of 2:1 in wheat flour and fed to animal once a day to induce heat. For retension of placenta, 34.17 per cent of the respondents fed extract obtained from tea leaves (Camellia sinensis) on boiling after sieving to animals. As far as ITKs regarding feeding practices are concerned 40.83 per cent of the respondents fed boiled Ber leaves (Ziziphus mauritiana) once a day to increase milk production. The study reveals that 42.50 per cent of respondents fed 10-12 leaves of Katori (Xylosona longifolium) plant to animals having diarrhoea and 15.83 per cent fed fruits of bill (Aegle marmelos) to animals having diarrhoea.